Risk Factors for Pulmonary Air Leak and Clinical Prognosis in Patients With COVID-19 Related Acute Respiratory Failure: A Retrospective Matched Control Study - Tonelli, Roberto; Bruzzi, Giulia; Manicardi, Linda; Tabbì, Luca; Fantini, Riccardo; Castaniere, Ivana; Andrisani, Dario; Gozzi, Filippo; Pellegrino, Maria Rosaria; Trentacosti, Fabiana; Dall’Ara, Lorenzo; Busani, Stefano; et al. (Frontiers in Medicine, 2022)
Abstract Background The role of excessive inspiratory effort in promoting alveolar and pleural rupture resulting in air leak (AL) in patients with SARS-CoV-2 induced acute respiratory failure (ARF) while on spontaneous breathing is undetermined. Methods Among all patients with COVID-19 related ARF admitted to a respiratory intensive care unit (RICU) and receiving non-invasive respiratory support, those developing an AL were and matched 1:1 (by means of PaO2/FiO2 ratio, age, body mass index-BMI and subsequent organ failure assessment [SOFA]) with a comparable population who did not (NAL group). Esophageal pressure (ΔPes) and dynamic transpulmonary pressure (ΔPL) swings were compared between groups. Risk factors affecting AL onset were evaluated. The composite outcome of ventilator-free-days (VFD) at day 28 (including ETI, mortality, tracheostomy) was compared between groups. Results AL and NAL groups (n=28) showed similar ΔPes, whereas AL had higher ΔPL (20 [16-21] and 17 [11-20], p=0.01 respectively). Higher ΔPL (OR=1.5 95%CI[1-1.8], p=0.01), positive end-expiratory pressure (OR=2.4 95%CI[1.2-5.9], p=0.04) and pressure support (OR=1.8 95%CI[1.1-3.5], p=0.03), D-dimer on admission (OR=2.1 95%CI[1.3-9.8], p=0.03), and features suggestive of consolidation on computed tomography scan (OR=3.8 95%CI[1.1-15], p= 0.04) were all significantly associated with AL. A lower VFD score resulted in a higher risk (HR=3.7 95%CI [1.2-11.3], p=0.01) in the AL group compared with NAL. RICU stay and 90-day mortality were also higher in the AL group compared with NAL. Conclusions In spontaneously breathing patients with COVID-19 related ARF, higher levels of ΔPL, blood D-dimer, NIV delivery pressures and a consolidative lung pattern were associated with AL onset.